An energy-efficient form-stable phase change materials synthesis method to enhance thermal storage and prevent acidification of cementitious composite. (19th September 2022) - Kumar, Dileep; Alam, Morshed; Sanjayan, Jay
Highlights: Proposed a procedural modification to prepare form-stable PCM composite. Proposed procedure increased PCM percentage and energy efficiency of the process. Capric Acid PCM caused acid attack when leaked into the cementitious composite. Acidification test was recommended to prepare PCM integrated cementitious composite. Introduced loading rate as a new factor for form shape stablized PCM composite synthesis. Abstract: Integration of Form-Stable Phase change materials (FSPCM) in building construction materials has been reported to have significant potential to improve building energy efficiency and reduce emissions from this sector. Previous studies on FSPCM only focused on increasing the PCM absorption rate as the performance criteria of FSPCM without considering the energy required to produce such composites. Moreover, the existing leakage performance test used while developing FSPCM is not 100 % reliable in detecting PCM leakage in cementitious materials, which may cause an acid attack and reduce concrete strength. Therefore, this study proposed a modification of existing FSPCM synthesizing methods to improve thermal storage, minimize the embodied energy of FSPCM composites and an acidification test to detect PCM leakage. The proposed method resulted in 75 % absorption of Capric acid PCM in porous hydrophobic expanded perlite (HEP). Moreover, the thermal storage of the prepared CAHEP PCM composite was found to be higher (ΔHm = 136.9 J/g, ΔHs = 134.4 J/g) due to higher PCM absorption. The prepared CAHEP form-stable PCM composite was chemically and thermally stable as observed from a series of standard characterization tests. The loading factor (the ratio of PCM absorption and energy consumed by the process) was found to be three times the existing methods making the proposed method more energy efficient. The compressive strength of CAHEP incorporated cementitious composite and its thermal conductivity increased with increasing PCM absorption. However, at 75 % CA absorption, both the compressive strength and thermal conductivity of the cementitious composite decreased due to acid attack by leaked CA PCM as observed in the acidification test, although the standard leakage test did not show any sign of leakage. No such acid attack was observed for the paraffin PCM composite.